PARAMETRIC STUDY OF LANDFILL STABILITY BY USING LIMIT EQUILIBRIUM METHOD - Danang Setiya Raharja (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2024)
A landfill is an example of essential geotechnical constructions that support human life in controlling waste processing. The height of landfill in Indonesia has reached tens of meters, as reviewed in this article, which is 60 m. The stability of the slopes of the landfill is a critical matter that needs to be studied to ensure that the landfill remains standing firmly and that landslides do not occur, which can cause huge losses both financially and even to the point of loss of life. One of the slope analysis methods is the Limit Equilibrium Method (LEM) with a two-dimensional (2D) model using a computer program. Stratigraphy and origin soil parameters were obtained from the results of field and laboratory test interpretations and parameter correlations. The landfill parameters will be varied into three types, lower bound with values c'=3 kPa and ϕ' = 210, medium bound with values c'=4 kPa and ϕ' = 250, and upper bound with values c'=6 kPa and ϕ ' = 300. The landfill slope is varied into five models with a ratio of vertical dimensions as 1 and horizontal dimensions as 1, 1.5, 2, 2.5, and 3. The analysis will be carried out in two conditions: static and dynamic. With several limitations and simplifications of the model, such as uniform landfill parameters for a total height of 60 m, this parameter study can still provide insight into the pattern of the slope of the landfill slope that meets the minimum stability criteria both in static and dynamic conditions. The analysis results show that the landfill's safe slope is 1:3.0 (V:H) with a few notes for the type of lower bound landfill parameter.